EFEKTIVITAS PELATIHAN TERHADAP PENGEMBANGAN TECHNICAL SKILL KARYAWAN BAGIAN PRODUKSI PT. MCDERMOTT INDONESIA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Shinta Wahyu Hati; Ryza Dwi Mayasari (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2019)
The purpose of this study is to desccribe and analyse the effectivity of training method for employee technical skill development that has given by PT McDermott Indonesia. This research type is explanatory research. This training method has given and used to measuring how far the technical skill has develop as long as the employee working at PT McDermott Indonesia. As for some of the measurement tools used by the training program at PT. McDermott Indonesia is evaluation (Assessment). This research using the method of path analysis conducted in the Department of Craft Training Centre PT. McDermott Indonesia amounting 115 respondents using a Purposive Sampling technique. Data collected directly by questionnaire, interviewed and observation at PT. McDermott Indonesia. The results showed the influence of effectiveness on the job training towards job satisfaction is 29.3% (sig 0.001 < 0.05); off the job training partially effect significantly to job satisfaction is 45.5% (sig 0000 < 0.05); effectiveness on the job training to the development of technical skill partially has no affect significant way and values of 7.6% (sig 0393 > 0.05); the effectiveness of off the job training towards the development of technical skill partially significantly influential amounted to 19.1% (sig 0047 < 0.05); on the job training, off the job training and job satisfaction simultaneously effect significantly towards the development of technical skills amounted to 46.4% (sig 0000 < 0.05).